Ante-Nicene Christian library: translations of the writings of the Fathers down to A.D. 325 - Roberts, Alexander; Donaldson, James (T. and T. Clark, 1867)
Vol. 1. Apostolic fathers -- v. 2. Justin Martyr & Athenagoras -- v. 3. Tatian, Theophilus, & Clementine Recognitions -- v. 4. Clement of Alexandria, v. 1 -- v. 5. Irenaeus, v. 1 -- v. 6. Hippolytus, Bp. of Rome, v. 1 -- v. 7. Tertullianus against Marcion -- v. 9. Irenaeus, v. 2 ; Hippolytus, v. 2 : fragments of the 3d century -- v. 10. Writings of Origen -- v. 11. Writings of Tertullian, v. 1 -- v. 12. Clement of Alexandria, v. 2 -- v. 13. Writings of Cyprian, v. 2 -- v. 14. Writings of Methodius -- v. 15. Writings of Tertullian, v. 2 -- v. 16. Apocryphal gospels, acts, & revelations -- v. 17. Clementine homilies, Apostolic constitutions -- v. 18. Writings of Tertullian, v. 3 : with the extant works of Victorinus & Commodianus -- v. 19. The seven books of Arnobius adversus gentes -- v. 20. Writings of Gregory Thaumaturgus, Dionysius of Alexandria, and Archelaus -- v. 21. Works of Lactantius, v. 1 -- v. 22. Works of Lactantius, v. 2 -- v. 23. Origen contra Celsum -- v. 24. Early liturgies and other documents.